PROFESSIONAL COUNSELLORS: ABILITY TO HELP MANAGE STRESS FOR ADJUSTMENT TO THE WORLD OF WORK - Ticka Herawati Azizah; Agus Supriyanto; Bambang Suprihatin; Nurlita Hendiani (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Individuals must have careful preparation and planning to enter the world of work. Individuals need the ability to manage stress to adjust to the world of work so that individuals can know the work environment. This article is structured to outline the importance of focusing on adapting to the world of work. Collector study using literature study through national, international journals and books that have been implemented. The results of this study indicate that managing stress is necessary in adjusting to the world of work. The impact of anxiety isn’t handled with beneficial effects in depression. Adjustments are made to order pressure to make the individual comfortable in the existing environment. Counsellors can assist individuals in managing stress to dealing with adjustments in work.